Contribution to the knowledge of genus Nalassus Mulsant, 1856 (Coleoptera: Tenebrionidae) from the Eastern Caucasus, Russia - Nabozhenko, Maxim V.; Gadaborsheva, Mariam A. (Zootaxa, 2023)
A new species of darkling beetle of the tribe Helopini is described from the Eastern Caucasus (Russia): Nalassus magomedrasuli Nabozhenko sp. n. It was originally described as the Dagestan population of N. kalashiani Nabozhenko, 2001 based on the similar structure of the male aedeagus. The new species is similar to N. kalashiani in that it differs in the structure of the eyes, male antennae, the shape of the pronotum, the scutellar shield, the male abdomen and habitats. Nalassus magomedrasuli occurs in xerophytic limestone mountain phryganoid steppes in Dagestan, whereas N. kalashiani is distributed in wet alpine meadows in the Chechen Republic and Ingushetia (Russia). The female of N. kalashiani collected in the State Natural reserve “Erzi” (Ingushetia) is described for the first time.